Ministry Of Finance Decree No. 405 Of The Year 2018 Determining The Percentages Of Deduction For Account Of The Tax = وزارة المالية قرار رقم 405 لسنة 2018 بتحديد نسب الخصم تحت حساب الضريبة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic